1985
DOI: 10.1063/1.449039
|View full text |Cite
|
Sign up to set email alerts
|

Electronic aspects of the hydride transfer mechanism. A bi n i t i o analytical gradient studies of the cyclopropenyl-cation/lithium hydride model reactant system

Abstract: The electronic mechanisms of a model hydride transfer reaction are theoretically studied with ab inito RHF and UHF SCF MO procedures at the 4-31G basis set level and analytical gradient methods. The model system describes the reduction of cyclopropenyl cation to cyclopropene by the oxidation of lithium hydride to lithium cation. The molecular fragments corresponding to the asymptotic reactive channels characterizing the stepwise mechanisms currently discussed in the literature have been characterized. The bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Our previous results 16,19,20,23,73 on models of the dehydrogenase enzyme family show that two mechanisms are possible: a hydride ion mechanism and an electron transfer accompanied by a hydrogen atom migration. Within the diabatic approach used in our work, 16a, the electron-hydrogen atom mechanism appears to be a plausible path. On the other hand, Bertrán et al.…”
Section: Resultsmentioning
confidence: 87%
“…Our previous results 16,19,20,23,73 on models of the dehydrogenase enzyme family show that two mechanisms are possible: a hydride ion mechanism and an electron transfer accompanied by a hydrogen atom migration. Within the diabatic approach used in our work, 16a, the electron-hydrogen atom mechanism appears to be a plausible path. On the other hand, Bertrán et al.…”
Section: Resultsmentioning
confidence: 87%
“…OH + has two unpaired electrons and no empty p orbital. Following the discussion of Tapia et al, 17 we expect the hydride transfer mechanism to first involve electron transfer, which is then followed by hydrogen atom transfer. In the present system, ground state OD + +C 3 H 6 on the triplet surface may first undergo rapid charge transfer.…”
Section: Computational Resultsmentioning
confidence: 96%
“…Quantum chemical studies [23,24] have shown a hydride ion as the most likely structure for this set of transferred particles. In this case the environment to the exchang ing centers has to be hydrophobic, otherwise, the hydride ion could react with a water mol ecule to produce molecular hydrogen, with particularly nasty consequences for the bio system.…”
Section: Discussionmentioning
confidence: 99%